Online teaching and learning in a graduate course In nursing education - NS Gwele (AOSIS, 2000)
Information technology has a potential to be the answer to one of Africa's most pressing problems- providing education to a number of geographically dispersed learners, who currently have to leave their countries for a number of years in order to pursue their studies elsewhere. The School of Nursing at the University of Natal launched an online graduate course in nursing education at the beginning of the year 2000 for the first time as part of a masters degree programme. A number of lessons have been learned from this experience. Firstly, it took too long to arrive at 'closure' on discussion of any one particular theme. There seemed to be a perpetual feeling of never "completing" teaching/learning tasks. Ordinarily, in a face-to-face (f2f) classroom, a particular theme or topic is scheduled for a particular lecture period. More often than not, whether clarity and/or resolution has been attained, the discussion moves on to the next theme, or topic. This has not been easy to do in computer mediated communication (CMC). The students' contributions, however, seemed more thought out and more focused than had been the case in the f2f classes. Secondly, the essentiality/importance of structure became apparent very early. After an initial tentative and slow start, once the students felt comfortable with the computer "classroom" , the bulletin board was flooded with messages, necessitating re-thinking the original structure.